2001
DOI: 10.1128/mcb.21.7.2349-2358.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of Rad27 (FEN-1) in Restricting Short-Sequence Recombination

Abstract: Saccharomyces cerevisiae mutants lacking the structure-specific nuclease Rad27 display an enhancement in recombination that increases as sequence length decreases, suggesting that Rad27 preferentially restricts recombination between short sequences. Since wild-type alleles of both RAD27 and its human homologue FEN1 complement the elevated short-sequence recombination (SSR) phenotype of a rad27-null mutant, this function may be conserved from yeast to humans. Furthermore, mutant Rad27 and FEN-1 enzymes with par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
36
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 74 publications
5
36
0
1
Order By: Relevance
“…FEN-1 is also a key enzyme for preventing expansion and contraction of bi-or trinucleotide repeats (16 -19). More recently we have demonstrated that FEN-1 nuclease plays an important role in limiting short sequence recombination for yeast genome stability (20). All of these observations illustrate its critical roles in genome integrity.…”
mentioning
confidence: 84%
“…FEN-1 is also a key enzyme for preventing expansion and contraction of bi-or trinucleotide repeats (16 -19). More recently we have demonstrated that FEN-1 nuclease plays an important role in limiting short sequence recombination for yeast genome stability (20). All of these observations illustrate its critical roles in genome integrity.…”
mentioning
confidence: 84%
“…These observations are most consistent with the rad27-null mutation primarily affecting the creation of DNA damage. Previous studies have implicated Rad27 in the processing of recombination intermediates (Wu et al 1999;Negritto et al 2001;Kikuchi et al 2005;Zheng et al 2005). The results reported here do not support such a conclusion, perhaps, because the effects of increased chromosome breakage on our assays eclipse the effects on the processing of 175 6 11 130 6 10 rad3-102 rad27 1 pRS416 192 6 11 ND rad3-102 rad27 1 pJM3 189 6 11 ND Doubling times (DT) were determined at 30°as described in materials and methods and are reported as the median doubling time 62 standard errors in minutes from at least five independent trials.…”
Section: Discussionmentioning
confidence: 99%
“…In the rad27-null mutant, all consequences of defective lagging-strand synthesis are observed. For example, rad27-null mutant cells display increased levels of single-stranded DNA (Vallen and Cross 1995;Parenteau and Wellinger 1999), mutagenesis (Tishkoffet al 1997), microsatellite instability (Schweitzer and Livingston 1998;Xie et al 2001;Refsland and Livingston 2005), minisatellite instability (Kokoska et al 1998;Lopes et al 2006a), telomeric repeat instability (Parenteau and Wellinger 1999), and recombination (Tishkoff et al 1997;Symington 1998;Negritto et al 2001). Combining the rad27D-null allele with null mutations in a large number of HR genes leads to synthetic lethality, strongly suggesting the need for HR to rescue DNA replication defects in these cells (Tishkoff et al 1997;Symington 1998;Debrauwere et al 2001).…”
mentioning
confidence: 99%
“…Mutational studies in yeast have suggested that FEN1 restrains recombination between short DNA sequences (Negritto et al 2001) such as the flaps arising during strand displacement DNA synthesis on the lagging strand of the replication fork or during DNA repair. These findings are also consistent with the triplet repeat expansion phenotype observed on FEN1/Rad27 mutation (Liu et al 2004;White et al 1999) and with its involvement in long patch BER along with its partner PCNA (Frosina et al 1996).…”
Section: Fen1mentioning
confidence: 99%